The Effect of Family Support Toward Motivation in Following The Drugs Rehabilitation Program - Sukamto, Edi; Rasmun, Rasmun; Andi, Parellangi; Sutrisno, Sutrisno (Journal of Global Research in Public Health, 2019)
Background: Children were victims of drugs in Samarinda were at the high level. Some parents feel desperate, shame of the community environment, accompanying their children to consult to various places and it has definitely cost a lot. Efforts of mentoring and support to their children also produce different results. Some of their children, who have been taking drugs want to rehabilitate, but at the end being bored and depressed by the rules of the rehabilitation place. Objective: This study aims to determine the effect of family support on the motivation of patients in following the drug rehabilitation program. Methods: The design of this research is observational analytics by using a survey method. This study was conducted in Samarinda City by involving the Rehabilitation Center of National Narcotics Agency in Tanah Merah Samarinda, East Kalimantan, with the populations are 632 respondents and based on Gay and Diehl theory, it obtained the number of samples are 79 respondents. The data analysis method in this research used Structural Equation Models (SmartPLS) and t (t-test). Result: Based on the research result got the value of family support toward the motivation is 0.366 with the value of the t-statistic is 3.772 > 1.96. The dominant indicator that influences the family support is the indicator of opportunity for nurturance. The dominant indicator that gives effect to motivation is the desire for help indicator. Conclusion: Family support has a positive and significant impact on the motivation of patients with the drug abuse in following the rehabilitation program in Samarinda. The family is advised to maintain and increase supporting, the family is advised to maintain the dominant factor of the opportunity for nurturance and increase the attachment, reassurance of worth, reliable alliance, and guidance and patients are advised to maintain the dominant factor that is desired to be assisted and improve the problem recognition and treatment readiness